Blood Vessel-Targeted Therapy in Colorectal Cancer: Current Strategies and Future Perspectives - Jacobsen, Anne; Siebler, Jürgen; Grützmann, Robert; Stürzl, Michael; Naschberger, Elisabeth (Cancers, 2024)
The vasculature is a key player and regulatory component in the multicellular microenvironment of solid tumors and, consequently, a therapeutic target. In colorectal carcinoma (CRC), antiangiogenic treatment was approved almost 20 years ago, but there are still no valid predictors of response. In addition, treatment resistance has become a problem. Vascular heterogeneity and plasticity due to species-, organ-, and milieu-dependent phenotypic and functional differences of blood vascular cells reduced the hope of being able to apply a standard approach of antiangiogenic therapy to all patients. In addition, the pathological vasculature in CRC is characterized by heterogeneous perfusion, impaired barrier function, immunosuppressive endothelial cell anergy, and metabolic competition-induced microenvironmental stress. Only recently, angiocrine proteins have been identified that are specifically released from vascular cells and can regulate tumor initiation and progression in an autocrine and paracrine manner. In this review, we summarize the history and current strategies for applying antiangiogenic treatment and discuss the associated challenges and opportunities, including normalizing the tumor vasculature, modulating milieu-dependent vascular heterogeneity, and targeting functions of angiocrine proteins. These new strategies could open perspectives for future vascular-targeted and patient-tailored therapy selection in CRC.
CRIS-Team Scopus Importer:2024-03-22
Keywords: aflibercept; angiocrine; antiangiogenic treatment; bevacizumab; cancer; colorectal cancer; endothelial cells; fruquintinib; ramucirumab; regorafenib; tumor microenvironment; vascular heterogeneity; vasculature